2020
DOI: 10.1038/s41598-020-60234-9
|View full text |Cite
|
Sign up to set email alerts
|

Examining Reproductive Health Outcomes in Females Exposed to Polychlorinated Biphenyl and Polybrominated Biphenyl

Abstract: In 1973, accidental contamination of Michigan livestock with polybrominated biphenyls (PBBs) led to the establishment of a registry of exposed individuals that have been followed for > 40 years. Besides being exposed to PBBs, this cohort has also been exposed to polychlorinated biphenyls (PCBs), a structurally similar class of environmental pollutants, at levels similar to average US exposure. In this study, we examined the association between current serum PCB and PBB levels and various female reproductive he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 58 publications
(64 reference statements)
0
32
0
Order By: Relevance
“…Evidence on HC-PCB and birth outcomes is conflicting, which may be due to the numerous differences across the previous studies, e.g. study design, population characteristics, measure of and differences in level of exposure [ 4 , 6 9 , 39 , 44 – 48 ]. Currently, the risk assessment of airborne PCB exposure is based on the knowledge obtained on HC-PCBs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence on HC-PCB and birth outcomes is conflicting, which may be due to the numerous differences across the previous studies, e.g. study design, population characteristics, measure of and differences in level of exposure [ 4 , 6 9 , 39 , 44 – 48 ]. Currently, the risk assessment of airborne PCB exposure is based on the knowledge obtained on HC-PCBs.…”
Section: Discussionmentioning
confidence: 99%
“…Since their ban, much attention has been paid to the accumulation of higher chlorinated PCBs (HC-PCBs) in the food chain, which is thought to constitute the most important source of human exposure. Studies have demonstrated conflicting yet concerning results in regards to health effects of these PCBs [4][5][6][7][8][9]. It was however recently discovered that residents of PCB contaminated apartments have considerably higher blood levels of lower chlorinated PCBs (LC-PCBs) compared to residents of uncontaminated apartments [10,11], and as much as 63% of the total PCB body burden in exposed adults and 36% in exposed toddlers may be from inhaled LC-PCBs [12].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence on HC-PCB and birth outcomes is con icting, which may be due to the numerous differences across the previous studies, e.g. study design, population characteristics, measure of and differences in level of exposure [4,6,54,[7][8][9]45,[50][51][52][53]. Currently, the risk assessment of airborne PCB exposure is based on the knowledge obtained on HC-PCBs.…”
Section: Previous Literature and Mechanismsmentioning
confidence: 99%
“…Since their ban, much attention has been paid to the accumulation of higher chlorinated PCBs (HC-PCBs) in the food chain, which is thought to constitute the most important source of human exposure. Studies have demonstrated con icting yet concerning results in regards to health effects of these PCBs [4][5][6][7][8][9]. It was however recently discovered that a signi cant part of human exposure seems to come from airborne PCB congeners evaporating from contaminated indoor building materials [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…PCBs are implicated as risk factors for developing neurodevelopmental disorders (NDDs), which often have comorbid symptoms of bladder dysfunction [ 8 ]. PCBs have also been linked to deleterious changes in other health outcomes such as reproductive and immune function [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Detectable levels of PCBs are present in serum and tissue samples from humans [ 9 , 19 ] and livestock [ 20 ], as well as commercial milk [ 20 , 21 ], air [ 22 , 23 ] and water [ 24 ].…”
Section: Introductionmentioning
confidence: 99%